2011
DOI: 10.4049/jimmunol.1002932
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Human Antibody-Secreting Cells during Vaccinations and Respiratory Viral Infections Are Characterized by High Specificity and Lack of Bystander Effect

Abstract: Surges of serum antibodies after immunization and infection are highly specific for the offending antigen, and recent studies demonstrate that vaccines induce transient increases in circulating antibody-secreting cells (ASCs). These ASCs are highly enriched but not universally specific for the immunizing antigen, suggesting that a fraction of these ASCs could arise from polyclonal bystander stimulation of pre-existing memory cells to unrelated antigens. This model is proposed to explain maintenance of long-liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
100
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 35 publications
6
100
1
Order By: Relevance
“…The percentages of specific cells are consistent with the PB responses in influenza-immune patients infected with a new serotype of influenza (30). Moreover, Lee et al (38) recently reported that the PB response to respiratory syncytial virus and influenza virus infection measured by ELISPOT was remarkably Ag specific and showed little bystander activation.…”
Section: Discussionsupporting
confidence: 78%
“…The percentages of specific cells are consistent with the PB responses in influenza-immune patients infected with a new serotype of influenza (30). Moreover, Lee et al (38) recently reported that the PB response to respiratory syncytial virus and influenza virus infection measured by ELISPOT was remarkably Ag specific and showed little bystander activation.…”
Section: Discussionsupporting
confidence: 78%
“…1B). Taken together, these data show that active HIV replication is associated with and possibly responsible for the presence of ASCs in the blood and that percentages of HIV-specific ASCs are highest in early viremia, although these frequencies are much lower than in other acute viral infections (34)(35)(36)(37).…”
Section: Patientsmentioning
confidence: 58%
“…However, there are certain similarities between HIV and the other viruses that relate to kinetics of exposure and the Ig isotype of blood PBs. With regard to temporal relationships, the burst of PBs in the blood is surprisingly similar for most non-HIV viruses studied, occurring 6 to 7 days after infection or vaccination (34,35,37,53,54), although the duration that PBs remain present in the blood varies with the persistence of the pathogen (37,46,50). With regard to Ig isotype, PBs that circulate in the blood following parenteral immunizations are mainly IgG (29,32,34) and are likely transiting to and from draining lymph nodes and the spleen (55)(56)(57).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations